Beyond the Textbook: University Students' Perceptions of Webtoon as a Digital Medium for English Vocabulary Enrichment - Dwi Supariani; Edi Sunjayanto Masykuri; Ismawati Ike Nugraeni (Universitas Muhammadiyah Mataram, 2026)
Vocabulary acquisition constitutes a foundational element in English language learning, yet many learners encounter significant challenges in developing and retaining lexical knowledge. This study aimed to investigate university students’ perceptions of Webtoon—a digital comic application—as a supplementary medium for enhancing English vocabulary, specifically examining (1) how Webtoon facilitates vocabulary improvement and (2) which genre types are most effective for lexical development. Employing a qualitative approach with semi-structured interviews as the primary data collection instrument, six undergraduate students from the English Language Education program at a private university in Central Java were purposively selected and participated in this research. Data were transcribed verbatim and analyzed thematically through open coding, categorization, and member-checking procedures to ensure credibility. The findings demonstrate that Webtoon facilitates vocabulary development through three primary mechanisms: engaging narrative content, contextual learning supported by visual scaffolding, and exposure to real-life language use including colloquialisms and idioms. Furthermore, students reported positive attitudes toward Webtoon’s integration into their learning practices. Both formal- and informal-language genres were found to offer distinct advantages, suggesting that a balanced combination of genre types yields the most comprehensive vocabulary enrichment. These results underscore Webtoon’s potential as an innovative and motivating pedagogical tool in English language education.